2015
DOI: 10.3923/ajpsaj.2015.97.105
|View full text |Cite
|
Sign up to set email alerts
|

Adding Phytogenic Material and/or Organic Acids to Broiler Diets: Effect on Performance, Nutrient Digestibility and Net Profit

Abstract: A growth experiment was conducted to study performance, nutrients digestibility and economic efficiency of broiler chicks fed corn-soybean meal diets supplemented with a commercial phytogenic product (Bedgen 40 ) contained artichoke extract (Cynara scolymus), a commercial mixture of ® organic acids (Galliacid ) and a combination of both. Starter, grower and finisher diets were ® supplemented with two levels of both being 0 and 150 g tG artichoke extract and 0 and 600 g tG 1 1 organic acids in 2×2 factorial ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
3
4
0
Order By: Relevance
“…Moreover, the present results agreed with those of Hassan et al (2015). Bucław (2016) and Xia et al (2019) showed that dietary inulin supplementation boosted broiler growth performance and enhanced systemic metabolism of minerals and lipids.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, the present results agreed with those of Hassan et al (2015). Bucław (2016) and Xia et al (2019) showed that dietary inulin supplementation boosted broiler growth performance and enhanced systemic metabolism of minerals and lipids.…”
Section: Discussionsupporting
confidence: 90%
“…Artichoke extract improved the broiler performance of birds fed corn-soybean meal diets and enhanced the immune response (Hassan et al, 2015). In addition, Jerusalem Artichoke tubers had an affirmative influence on gut health, thus serving as a protective feed ingredient.…”
mentioning
confidence: 96%
“…The present study results showed that supplementation of phytobiotics enhanced the apparent ileal digestibility of DM, OM, EE, CP, and ash. These results are similar to the outcome of Hassan et al [72] and Farahat et al [73], where supplementation of phytobiotics, artichoke (Cynara scolymus), and grape seed tannin in broiler diets improved digestibility of DM, EE, and CP. Halquinol can slow peristalsis in the gut [43]; this slowed passage of food in the gut may help in enhanced absorption.…”
Section: Nutrient Digestibilitysupporting
confidence: 89%
“…Due to the differences in feeding habits and digestive potential, the activity of digestive enzymes varies in different fish species (Iqbal et al, 2016). Furthermore, organic acids are proving to be a promising dietary additive to improve intestinal health and growth performance (Hassan et al, 2015). Citric acid (CA) has become the one of the world's most usable organic acid (Sauer et al, 2008).…”
Section: Formulation Of Pellets and Feeding Techniquementioning
confidence: 99%